Pengaruh Pendekatan Steam dengan Model Problem Based Learning (PBL) terhadap Hasil Belajar Kognitif Siswa Pembelajaran IPA SDN 15 Singkawang - Astuti, Lisa; Mayasari, Dian; Setyowati, Rini (LP. Ma'arif Janggan Magetan, 2023)
This research aims to determine: 1) the difference in cognitive learning outcomes for classes that use the STEAM Approach with the Problem Based Learning (PBL) Model and classes that do not use the STEAM Approach with the Problem Based Learning (PBL) Model. 2) how big is the influence of the STEAM approach with the Problem Based Learning (PBL) model on the cognitive science learning outcomes of class VI students at SDN 15 Singkawang. The type of research is quantitative research with quasi experimental methods, in the form of Nonequivalent Control Group Design. The data collection technique uses a test technique in the form of essay questions on the characteristics of boys' and girls' puberty. The data analysis technique used was the t-test to look for sample differences and the effect size test to look for influence. The results of the prerequisite test analysis showed that the data was normally distributed. The results of the research show that t_count = 5.961 > t_tabel = 2.01536, which means there are differences in learning outcomes in the cognitive domain between students who applied the STEAM approach with the Problem Based Learning (PBL) model and classes that did not use treatment. The STEAM approach with the Problem Based Learning (PBL) model has a high influence on students' cognitive learning outcomes with the Effect Size test result = 1.802.